1998
DOI: 10.1021/ma9610368
|View full text |Cite
|
Sign up to set email alerts
|

Strength Development at the Interface of Amorphous Polymers and Their Miscible Blends, below the Glass Transition Temperature

Abstract: Bonding amorphous polystyrene (PS) and poly(2,6-dimethyl 1,4-phenylene oxide) (PPO) has been carried out in a broad range of temperatures and contact times (t), but always below the glass transition temperature (T g), in a lap−shear joint geometry. Strength at the symmetric and asymmetric polymer/polymer interfaces develops with t 1/4 and, hence, is diffusion controlled. The development of strength at the homopolymer/miscible blend interface below T g can be simulated from data for homopolymer/homopolymer inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 48 publications
(104 reference statements)
8
46
0
Order By: Relevance
“…Ten joints were placed side by side between two stainless steel plates and preheated for 1 rain in a Carver laboratory press, which had already been warmed up to the chosen bonding (or healing) temperature. A contact pressure of 0.8 MPa, as selected in [18], was then applied to the joints. To apply pressure to the interface as unlform]y as possible, the samples were sorted out so that the thickness of each joint was constant, at • ~tm.…”
Section: Introductionmentioning
confidence: 99%
“…Ten joints were placed side by side between two stainless steel plates and preheated for 1 rain in a Carver laboratory press, which had already been warmed up to the chosen bonding (or healing) temperature. A contact pressure of 0.8 MPa, as selected in [18], was then applied to the joints. To apply pressure to the interface as unlform]y as possible, the samples were sorted out so that the thickness of each joint was constant, at • ~tm.…”
Section: Introductionmentioning
confidence: 99%
“…Details about the experimental procedures of bonding and mechanical measurements can be found elsewhere. 10 The temperature-shift factor, which is necessary in the time-temperature analysis, can be either measured or calculated. 12 The calculation proposed by Williams et al 19 works generally well, but, unfortunately, the surface T g , which is required in this calculation, is unknown.…”
Section: Mechanical Measurementsmentioning
confidence: 99%
“…This process has been investigated mainly above the glass transition temperatures (T g ) of the two polymers involved, [1][2][3][4][5] between their two T g , 6 -8 and even below both of them, 9,10 since it has been shown that the effective T g in the surface layer of a polymer film is lower than the bulk T g , 11 at a depth of about a radius of gyration.…”
Section: Introductionmentioning
confidence: 99%
“…Prud'homme and co-workers used lap shear measurements to study the interface strength between PS/PS. [11][12] They observed the interfacial strength occurred well below T g , that is, below T g Ϫ40°C for polydisperse PS (high molecular weight of PS, M w ϭ 230,000, M w /M n ϭ 2.84) with thickness (100 m), whereas below T g Ϫ10°C for the monodisperse PS.…”
Section: Introductionmentioning
confidence: 99%